Solving PDEs with a Hybrid Radial Basis Function: Power-Generalized Multiquadric Kernel (Advances in Applied Mathematics and Mechanics, 2022)
Radial Basis Function (RBF) kernels are key functional forms for advancedsolutions of higher-order partial differential equations (PDEs). In the present study, ahybrid kernel was developed for meshless solutions of PDEs widely seen in severalengineering problems. This kernel, Power-Generalized Multiquadric — Power-GMQ,was built up by vanishing the dependence of $ε$, which is significant since its selection induces severe problems regarding numerical instabilities and convergence issues.Another drawback of $ε$-dependency is that the optimal $ε$ value does not exist in perpetuity. We present the Power-GMQ kernel which combines the advantages of RadialPower and Generalized Multiquadric RBFs in a generic formulation. Power-GMQ RBFwas tested in higher-order PDEs with particular boundary conditions and differentdomains. RBF-Finite Difference (RBF-FD) discretization was also implemented to investigate the characteristics of the proposed RBF. Numerical results revealed that ourproposed kernel makes similar or better estimations as against to the Gaussian andMultiquadric kernels with a mild increase in computational cost. Gauss-QR methodmay achieve better accuracy in some cases with considerably higher computationalcost. By using Power-GMQ RBF, the dependency of solution on $ε$ was also substantially relaxed and consistent error behavior were obtained regardless of the selected $ε$ accompanied.